ConCerv: a prospective trial of conservative surgery for low-risk early-stage cervical cancer. Issue 10 (7th October 2021) - Schmeler, Kathleen M; Pareja, Rene; Lopez Blanco, Aldo; Humberto Fregnani, Jose; Lopes, Andre; Perrotta, Myriam; Tsunoda, Audrey T; Cantú-de-León, David F; Ramondetta, Lois M; Manchana, Tarinee; Crotzer, David R; McNally, Orla M; et al.
Abstract : Objective: The objective of the ConCerv Trial was to prospectively evaluate the feasibility of conservative surgery in women with early-stage, low-risk cervical cancer. Methods: From April 2010 to March 2019, a prospective, single-arm, multicenter study evaluated conservative surgery in participants from 16 sites in nine countries. Eligibility criteria included: (1) FIGO 2009 stage IA2–IB1 cervical carcinoma; (2) squamous cell (any grade) or adenocarcinoma (grade 1 or 2 only) histology; (3) tumor size < 2 cm; (4) no lymphovascular space invasion; (5) depth of invasion < 10 mm; (6) negative imaging for metastatic disease; and (7) negative conization margins. Cervical conization was performed to determine eligibility, with one repeat cone permitted. Eligible women desiring fertility preservation underwent a second surgery with pelvic lymph node assessment, consisting of sentinel lymph node biopsy and/or full pelvic lymph node dissection. Those not desiring fertility preservation underwent simple hysterectomy with lymph node assessment. Women who had undergone an 'inadvertent' simple hysterectomy with an unexpected post-operative diagnosis of cancer were also eligible if they met the above inclusion criteria and underwent a second surgery with pelvic lymph node dissection only. Results: 100 evaluable patients were enrolled. Median age at surgery was 38 years (range 23–67). Stage was IA2 (33%) and IB1 (67%). Surgery included conization followed by lymph node assessment in 44 women, conization followed by simple hysterectomy with lymph node assessment in 40 women, and inadvertent simple hysterectomy followed by lymph node dissection in 16 women. Positive lymph nodes were noted in 5 patients (5%). Residual disease in the post-conization hysterectomy specimen was noted in 1/40 patients—that is, an immediate failure rate of 2.5%. Median follow-up was 36.3 months (range 0.0–68.3). Three patients developed recurrent disease within 2 years of surgery—that is, a cumulative incidence of 3.5% (95% CI 0.9% to 9.0%). Discussion: Our prospective data show that select patients with early-stage, low-risk cervical carcinoma may be offered conservative surgery.